Granzyme B-induced and caspase 3-dependent cleavage of gelsolin by mouse cytotoxic T cells modifies cytoskeleton dynamics - Martin, Praxedis Sina; Pardo, Julián; Schill, Natalie; Jöckel, Lars; Berg, Matthias; Froelich, Christopher J.; Wallich, Reinhard; Simon, Markus M. (The journal of biological chemistry, 2010)
Granule-associated perforin and granzymes (gzms) are key effector molecules of cytotoxic T lymphocytes (Tc cells) and natural killer cells and play a critical role in the control of intracellular pathogens and cancer. Based on the notion that many gzms, including A, B, C, K, H, and M exhibit cytotoxic activity in vitro, all gzms are believed to serve a similar function in vivo. However, more recent evidence supports the concept that gzms are not unidimensional but, rather, possess non-cytotoxic potential, including stimulation of pro-inflammatory cytokines and anti-viral activities. The present study shows that isolated mouse gzmB cleaves the actin-severing mouse protein, cytoplasmic gelsolin (c-gelsolin) in vitro. However, when delivered to intact target cells by ex vivo immune Tc cells, gzmB mediates c-gelsolin proteolysis via activation of caspases 3/7. The NH(2)-terminal c-gelsolin fragment generated by either gzmB or caspase 3 in vitro constitutively severs actin filaments without destroying the target cells. The observation that gzmB secreted by Tc cells initiates a caspase cascade that disintegrates the actin cytoskeleton in target cells suggests that this intracellular process may contribute to anti-viral host defense.
Gesehen am 17.05.2021